Pengenalan Instalasi Listrik yang Aman Kepada Siswa-Siswi SMPN 7 Mataram - Ni Made Seniari; Rosmaliati Rosmaliati; Supriyatna Supriyatna; Abdul Natsir; Ida Ayu Sri Adnyani; Sabar Nababan (Universitas Negeri Makassar, 2020)
Understanding of electrical installation and the use of electrical equipment that is proper and safe, has a big contribution to the safety and security around us. The introduction of safe electrical installations according to the Indonesian National Standard, namely the General Requirements for Electrical Installations (SNI: PUIL 2011) needs to be disseminated to the public from an early age. The problems were: (1) Socialization of electrical installations is less socialized to the wider community, (2) Socialization of SNI PUIL 2011 is less socialized by related parties, (3) There is no special curriculum that provides practical skills to junior high school students regarding safe electrical installations. External targets are students: (1) Can recognize the components of simple electrical installations in their homes, (2) Understand the functions and workings of installation components, (3) Understand the procedures for installing electrical installations, (4) Be able to plan installation installations electricity. The methods used were (1) lectures on understanding the importance of safe electrical installations, the functions and workings of installation components, (2) demonstrations using electrical installation module boards, (3) Questions and answers and discussions. The results achieved included students: (1) Understanding of simple electrical installations in their homes, (2) Understanding of electrical installation procedures and planning, (3) Being able to plan installations